Acute dextran sulfate sodium (DSS)-induced colitis promotes gut microbial dysbiosis in mice - Munyaka, Peris Mumbi; Rabbi, Mohammad Fazle; Khafipour, Ehsan; Ghia, Jean-Eric (Journal of basic microbiology, 2016)
The most widely used and characterized experimental model of ulcerative colitis (UC) is the epithelial erosion, dextran sulfate sodium (DSS)‐induced colitis, which is developed by administration of DSS in drinking water. We investigated fecal and colonic mucosa microbial composition and functional changes in mice treated with DSS. C57Bl/6 mice received 5% DSS in drinking water for 5 days. Inflammation was evaluated clinically and by analysis of colonic tissue cytokine levels and C‐reactive protein (CRP) in the serum. Colonic mucosa and fecal samples were used for DNA extraction and the V4 region of bacterial 16S rRNA gene was subjected to MiSeq Illumina sequencing. Alpha‐ and beta‐diversities, and compositional differences at phylum and genus levels were determined, and bacterial functional pathways were predicted. DSS increased disease severity, serum CRP and cytokines IL‐1β and IL‐6, but decreased bacterial species richness, and shifted bacterial community composition. Bacteroides, Turicibacter, Escherichia, Clostridium, Enterobacteriaceae, Clostridiaceae, Bacteroidaceae, Bacteroidales, among other taxa were associated with DSS treatment in fecal and colonic samples. Also, DSS altered microbial functional pathways in both colonic mucosa and fecal samples. Conclusions: The development of colitis in DSS model was accompanied with reduced microbial diversity and dysbiosis of gut microbiota at lower taxonomical levels.